SENSITIVITY OF SINGLE-CRYSTAL FOIL FATIGUE INDICATORS - Karuskevich, Mikhail; Maslak, Tatiana; Hayday, Genady (Proceedings of National Aviation University (archive), 2006)
It was shown that practical application of single-crystal foil fatigue indicators requires the possibility to control their sensitivity to mechanical loads. It was proved that the single- crystal and separate grain fatigue characteristics significantly depend on their crystallographic orientation.